Pendampingan Keterampilan Media Pembelajaran dalam Menghafal Mufradat Bahasa Arab - Zainuri, Zainuri; Jannah, Hilmi Mufidah Afiyatul (INAIFAS Press, 2023)
This assistance is provided to students of Madrasah ibtidaiyyah who live in wonosari village, puger subdistrict. To eliminate the thought of the difficulty of learning Arabic and memorizing it, students need assistance that is directed to self-creativity through the talents of the skills they have such as learning to memorize mufrodat about limbs by making paper miniatures that can be used in every lesson, especially at the basic education level and generally for various levels of education. This service research uses the community development method. The results of this mentoring activity showed an increase in motivation to memorize Arabic mufrodat and foster creativity in the mentor.